Italy : Staff Report for the 2011 Article IV Consultation; Informational Annex; Public Information Notice; Statement by the Staff Representative; and Statement by the Executive Director for Italy. (IMF Staff Country Reports; Country Report ;, 2011)
Italy's economic development after the recession is analyzed in this study. Earnings were hampered by low net interest and high loan-loss provisions, but banks remained profitable. A large and stable retail funding base and ample collateral to access eurosystem refinancing helped Italian banks to face liquidity and funding risks. The tax system was simplified to support growth and enhance tax compliance. The execution of fiscal federalism should not undermine fiscal discipline, and measures were taken to improve employment. Flexibility introduced by the labor market was welcomed.